2017
DOI: 10.4172/2329-9509.1000189
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated With Decreased Bone Mineral Density in Young and Middle-Aged Male Schizophrenic Patients

Abstract: Objective: The prevalence and factors of decreased bone mineral density (BMD) in young and middle-aged schizophrenic male subjects were examined in this study. Methods:The sample included male patients, diagnosed with schizophrenia, between 18 and 45 years old. In the large-sample, cross-sectional study, cluster sampling method was adopted. 200 male inpatients in total, between 18 and 45 years old, diagnosed with schizophrenia, were included and interviewed in Beijing. The clinical assessment instruments inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…1 C). Our findings are consistent with previous studies of Shen, , et al 10 , who reported that male schizophrenic subjects had a higher prevalence of decreased BMD compared with the healthy population in china. Cui, et al 28 also found that BMD decreased remarkably in Chinese patients with schizophrenia.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…1 C). Our findings are consistent with previous studies of Shen, , et al 10 , who reported that male schizophrenic subjects had a higher prevalence of decreased BMD compared with the healthy population in china. Cui, et al 28 also found that BMD decreased remarkably in Chinese patients with schizophrenia.…”
Section: Discussionsupporting
confidence: 93%
“…BMD and other bone turnover marker levels in schizophrenia patients should be studied in the future. Third, as previous studies has reported, reduced BMD in schizophrenia is associated with several factors such as smoking, physical activity, and alcohol consumption or other substance abuse 1,2,4,10,11 . However, due to the limitations of our study, we did not collect these data , which deserve future investigations.…”
Section: Limitationsmentioning
confidence: 79%
See 2 more Smart Citations